البناء الدلالي للقصة عند نجيب الكيلاني: "ابن سبيل" نموذجا The Novel’s Semantic Structure in Najib al-Kaylani’s Works with reference to Ibn SabÊl - (Jamal Hadri), جمال حضري (At-Tajdid - Intellectual Refereed Journal, 2014)
تنطلق هذه الدراسة من اعتبار دلالة النص نتيجة لبنائه وعلاقات مكوناته اللغوية، متجاوزة المنظور الإفرادي، الذي يحتفل بالجزئيات ويستغرق في البحث عن مدلولاتها الخاصة، دون الانتباه إلى كون المجاورات النصية حاسمة في تحيين معاني واستبعاد أخرى. ومن ثم فإن تحليل النص القصصي المختار، وهو قصة "ابن سبيل" لنجيب الكيلاني، قد وظف أدوات تعنى أساسًا بالتقاط وقائعه منظورًا إليها في تظافرها النصي. فكانت المسارات الصورية عوض الأحداث المجتزأة، وكانت التشاكلات الدلالية والسيميائية، عوض نوى المعنى المبعثرة في أرجائه. ثم كان البحث عن تواشج تلك التشاكلات داخل المسارات، مما كشف عن نسيج متشابك كانت خيوطه هي المحاور الدلالية التي يخترق بعضها بعضًا، بحيث تنبث في البنية الكلية للقصة. وقد وفر المنهج السيميائي من خلاله تصوره العلائقي للنص وأدواته التحليلية المكافئة لهذا التصور أدوات مختلفة، حاولت الدراسة تطويعها لتواكب النص ولا تفرض عليه قوالبها، خاصة إذا كان هذا النص ينبض بالحيوية الإيمانية والقيم الأخلاقية. وبذلك نجح الباحث في أن تكون مقاربته وفية للنص وهو يرسم نماذج أخلاقية رفيعة، دون التفريط من جهة أخرى في القيمة الإجرائية والدراسية للمنهج، وهذا لب الهدف الذي انطلق البحث لتحقيقه، ألا وهو استثمار المستجد النقدي وتطويعه وتوطينه أو تطعيمه بما تقتضيه طبيعة النص المدروس. الكلمات الأساسية: عامل، ممثل، خطابي، مسار صوري، تشاكل دلالي، تشاكل سيميائي، علاقة، سياق، تماثل، مخالفة. _______________________________ The presents study takes as its starting point the idea that a text’s semantics is the result of its structure as well as of the interrelationships of its linguistic components. It thus transcends the piecemeal approach that focuses on particulars and delves into unearthing their special denotations without realizing that textual adjacencies play the decisive role in sanctioning certain meanings to the exclusion of others. Accordingly, our analysis of NajÊb al-KaylÉnÊ’s novel Ibn SabÊl has employed a set of tools that are mainly concerned about examining its events in their textual contiguity and coalescence. Hence, image unfolding processes and semantic and semiotic structural similarities have been emphasized instead of de-contextualized events and atomized connotations scattered throughout the narrative. Then, an examination of the interrelatedness of the structural similarities in the unfolding processes was carried out. All this enabled us to discover in the object of study an inter-woven texture of meanings the threads of which consist of semantic themes that interpenetrate, thus permeating the total structure of the novel. Through its structural conception of the text and its correspondent analytical tools, semiotics has provided the study with various tools that have been adapted in order to suit the text in question rather than forcing that text into the moulds of semiotics, especially seen the fact that the novel is so animated with dynamic faith and morality. Likewise, the author has succeeded in keeping his approach faithful to a text whose purpose is to portray high moral archetypes, without however compromising the academic value and operational function of the semiotic method. Such has been the goal pursued in this study: to make use of new critical methods by adapting, developing, and adjusting them in accordance with the nature of the text under examination. Key words: agent, character, discursive, rhetorical, image unfolding processes, semantic structural similarity, semiotic similarity, connection, context, similarity, difference.